« Le train qui siffle ». Nostalgie et modernité dans la chanson country-western au Québec - Lefrançois, Catherine (Volume !, 2014)

Pour ne pas chanter idiote. Quand les Cultural Studies et la perspective féministe se marient - Boisclair, Isabelle (Françoise Stéréo, 2014)
Keywords: Pas de lien web

Women in Leonard Cohen's Work - Álvarez Pérez, Maria Icíar (Multidisciplinary Views on Popular Culture: Proceedings of the 5th International Selicup Conference, 2014)

Glimpses Into My Compositional Style and Techniques : Text and Musical Examples - Badian, Maya (Lucian Badian Editions, 2014)

La Bolduc en tournée : un patrimoine matériel unique - Boulay, Vicky (Magazine Gaspésie, 2014)
An article from Magazine Gaspésie, on Érudit.
Publisher: Musée de la Gaspésie

Shock, glam, punk - Desfossés, Félix B. (No Speed Limit (1964-1989). L’évolution du métal québécois, 2014)

Soprano Pierrette Alarie (1921-2011), tenor Léopold Simoneau (1916-2006). Part 1 - Duffie, Bruce (Opera Journal, 2014)
Keywords: Interviews; Music; Musical performances; Musicians & conductors; Singers

Soprano Pierrette Alarie (1921-2011), tenor Léopold Simoneau (1916-2006). Part 2 - Duffie, Bruce (Opera Journal, 2014)
Keywords: Accompanists; Composers; Librettists; Music; Musical performances; Musicians & conductors; Opera; Singers

Les Daraîche, la famille royale du country - Dumas, Carmel (Magazine Gaspésie, 2014)
Un article de la revue Magazine Gaspésie, diffusée par la plateforme Érudit.

Michel Louvain. Sans âge - Gignac, Benoît (Éditions Caractère, 2014)
Découvert au milieu des années 50, admiré et adulé, Michel Louvain fait encore battre les coeurs près de 60 ans après avoir amorcé sa carrière. Ce livre-coffret retrace le parcours irréprochable de cet artiste accompli, qui a remporté les honneurs autant pour ses performances sur disque, sur scène et à la télévision que pour son soutien à des causes sociales.

Claude Vivier: A Composer’s Life - Gilmore, Bob (University of Rochester Press, 2014)
Claude Vivier's haunting and expressive music has captivated audiences around the world. But the French-Canadian composer is remembered also because of the dramatic circumstances of his death: he was found murdered in his Paris apartment at the age of thirty-four. Given unrestricted access to Vivier's archives and interviews with Vivier's family, teachers, friends, and colleagues, musicologist and biographer Bob Gilmore tells here the full story of Vivier's fascinating life, from his abandonment as a child in a Montreal orphanage to his posthumous acclaim as one of the leading composers of his generation. Expelled from a religious school at seventeen for "lack of maturity," Vivier gave up his ambition to join the priesthood to study composition. Between 1978 and 1981 Vivier wrote the works on which his reputation rests, including 'Lonely Child', 'Bouchara', and the operas 'Kopernikus' and 'Marco Polo'. He went to Paris in 1982 to work on a new opera, the composition of which was interrupted by his murder. On his desk was the manuscript of his last work, uncannily entitled "Do You Believe in the Immortality of the Soul?" Vivier's is a tragic but life-affirming story, intimately connected to his passionate music. Bob Gilmore is a musicologist and performer and teaches at Brunel University in London. He is the author of 'Harry Partch: A Biography'.

Le Lunatique, « Le temps du changement » : Intimidation, ostracisme et homophobie dans le milieu hip-hop au Québec - Lamort, Kapois (Les boss du Québec. R.A.P. du fleur de lysée. Analyse socio-historique et sociologique du hip-hop dans la société québécoise, 2014)
Le tout premier livre monographique et scientifique axé sur la culture Hip-Hop au Québec, rédigé par Kapois Lamort, historien spécialiste diplômé de l’Université du Québec à Montréal ( UQAM); cet ouvrage retrace les 35 ans d’existence du H.I.P.H.O.P. à travers la société québécoise de 1979 à 2015

Mad Je Deviendrai : Les divas dans le hip-hop au Québec - Lamort, Kapois (Les boss du Québec. R.A.P. du fleur de lysée. Analyse socio-historique et sociologique du hip-hop dans la société québécoise, 2014)
Keywords: Italique avant les deux-points

Pétassetissité : Contenu explicite et lyrisme sexuel dans le hip-hop au Québec - Lamort, Kapois (Les boss du Québec. R.A.P. du fleur de lysée. Analyse socio-historique et sociologique du hip-hop dans la société québécoise, 2014)
Keywords: Italique avant les deux-points

Rap, langues, « québéquicité » et rapports sociaux de sexe : pratiques et expériences de rappeuses montréalaises d’origine haïtienne - Lesacher, Claire (Diversité urbaine, 2014)
In the stories recounting the early days of the rap scene in Montreal, actors of Haitian descent were particularly active on the rap scene: this is evident in rap texts, where frequent occurrences of Haitian Creole can be found. Considering this characteristic of Montreal rap, we propose a reflection on the issues around the visibility of Haitian migrants, and descendants of Haitian migrants, in Quebec public space by focusing on the practices and experiences of Montreal female rappers of Haitian descent. In this contribution, which aims at understanding the processes of hegemonization and minoritization at work in the Montreal and Quebec context, we will examine in particular how the vectors of differentiation involving language, “québéquicité” or gender, are manifested and reproduced in the media coverage of artistic productions.
Keywords: Haitian community; Rap; communauté haïtienne; gender; genre; languages; langues; « québéquicité »; “québéquicité”

Translanguaging in the Multilingual Montreal Hip-Hop Community: Everyday Poetics as Counter to the Myths of the Monolingual Classroom - Low, Bronwen; Sarkar, Mela (Heteroglossia as Practice and Pedagogy, 2014)
This chapter explores the possibilities multilingual hip-hop offers for language instruction within multiethnic classrooms in Montreal shaped by multiple discursive practices. The authors review current research on multilingualism and teaching and propose strategies for overcoming the French prescriptivist monolingual mindset in education in Quebec. They also turn to poetics, and in particular the literary theory of Edouard Glissant (Caribbean discourse, 1989; Poetics of relation, 1997) and the Martinican school of Créolité, offering possibilities for rethinking relationships between oral and written, vernacular and standard language forms and for igniting language teachers’ pedagogic imaginations.
Keywords: Creolization; Hip-hop; Oraliture; Popular culture

Le powwow contemporain dans l’est du Canada : une pratique du rassemblement - Mailhot, Amélie-Anne; Giroux, Dalie (Les arts performatifs et spectaculaires des Premières Nations de l’est du Canada, 2014)

In Search of a Different History: The Remains of Burlesque in Montreal - Mansbridge, Joanna (Canadian Theatre Review, 2014)
: Taking Elin Diamond’s and Rebecca Schneider’s recent work in drama and performance studies as a starting point, this essay looks at two eras of burlesque in Montreal—the 1940s-50s and 2012—tracing a shifting landscape of popular entertainment, politics, religion, and social attitudes toward female sexuality. There is a central question underlying this examination: Why burlesque? Why now (or, rather, again?). I argue that burlesque offers an archive that evokes a different, more glamorous history than the one passed down to women by second-wave feminism. Burlesque also provides an alternative to popular culture’s commodification of female sexuality, technology’s mediation of social life, and heteronormative culture’s privatization of sexuality, giving women—and men—a stage on which to make fun of our cultural fixation with sex and the female body. Both nostalgically looking back and eagerly reaching for the new, neo-burlesque repeats the past as it simultaneously reinvents it.
Publisher: University of Toronto Press

L'enjeu des communautés en sociomusicologie : Le cas du projet de recherche sur le développement des publics de la musique au Québec - Marcoux-Gendron, Caroline; Couture, Ariane; Gervasi, Flavia; Duchesneau, Michel (MUSICultures, 2014)

Nicole Lizée. Faisceaux imaginaires et cool media - McKinley, Maxime (La création musicale au Québec, 2014)

Interpreting Brazilianness: Reception and Representation in the Brazilian Music Scenes of Toronto and Montreal - Mercier, Catherine G. (Université de Toronto, 2014)
In Toronto and Montreal, Brazilian popular music performances constitute a context for intercultural encounter. Performances offer Brazilians the opportunity to present their culture of origin while emphasising their identification with it. The issue of representation is quite complex, however, due to the involvement of a majority of non-Brazilian musicians, audience members, artistic directors, producers, promoters, and journalists. This dissertation focuses on music reception and cultural representation and how these may influence each other after music has been decontextualised and recontextualised. I look closely at local non-Brazilian audiences possessing different degrees of familiarity with Brazilian music, and I demonstrate how cultural stereotypes influence their conceptions and expectations of Brazilian music, culture, and people. I argue that a desire for cultural difference and the exotic, encouraged by discourses of cultural diversity, influences the reception of performances. I suggest that, through the privileged gaze of non-Brazilian attendees, performances may be adjusted to correspond to audience fantasies of Brazil. Some non-Brazilians would like to become knowledgeable of, and even intimate with Brazilian culture, which would satisfy their desire to be cosmopolitan. However, pleasure frequently matters more to them than a nuanced understanding of Brazilian culture; this explains, I contend, why some Torontonians and Montrealers have become comfortable with essentialist and stereotypical representations. I examine how some non-Brazilian musicians, promoters, and band agents reinforce mythologies of Brazil to meet audience demands and sometimes to satisfy their own fantasies. I analyse the reproduction of similarly problematic discourses on Brazil in the presentations of Brazilian artists as both a form of autoexoticism and a particular type of tactical or strategic essentialism. Rather than to represent and understand Brazilian culture, I argue that, through local music performances, Brazilians and non-Brazilians in Toronto and Montreal interpret Brazilianness.

“We Paved the Way for Whatever Tolerance They Have in Their Lives”: An Interview with Michelle De Ville, “The First Door Bitch in Montreal” - Namaste, Viviane (Trans Activism in Canada: A Reader, 2014)
Centring the voices and experiences of trans identified people as experts on their own lives and agents of change, Trans Activism in Canada opens up a dialogue between scholars and community members in an effort to improve the lives of sex and gender variant people

Le voyage, la danse et la représentation des femmes dans la culture de grande consommation (1936-1947) - Savoie, Chantal (Les Cahiers de l'IREF, 2014)

Jazz, Diaspora and the History and Writing of Black Anglophone Montreal - Siemerling, Winfried (Critical Collaborations: Indigeneity, Diaspora, and Ecology in Canadian Literary Studies, 2014)

'The digital is everywhere': Negotiating the aesthetics of digital mediation in Montreal's electroacoustic and sound art scenes - Valiquet, Patrick Joseph (Université d'Oxford, 2014)
In this thesis I argue that the relationship between the increasing ubiquity of digital audio technologies and the transformation of aesthetic hierarchies in electroacoustic and sound art traditions is not deterministic, but negotiated by producers and policy-makers in specific historical and cultural contexts. Interviews, observations, and historical data were gathered during sixteen months of ethnographic fieldwork in the Canadian city of Montreal between 2011 and 2012. Research was conducted and analysed in collaboration with a transnational group of researchers on a programme of comparative research that tracked global changes to music and musical practice associated with digital technologies. The introduction presents Montreal as a rich ecology in which to track struggles for aesthetic authority, detailing its history as a key site of electroacoustic and sound art production, and its local positioning as a politically strategic 'hub' for the Canadian culture industry. Core chapters examine the specific role of digital mediation in the negotiation of electroacoustic and sound art aesthetics from multiple interlocking perspectives: the recursive relationship between technological affordances and theories of mediation; the mobilisation of digital technologies in the delineation of cultural, professional and generational territories; the political contestation of digital literacies and pedagogies; the articulation of the digital's opposition with analogue in the construction of instruments and recording formats; and the effects of the digital on the dynamics of genre and genre hierarchies. The concluding chapter offers a critique of the notion that digital mediation has shifted the balance between the normative and the generative dimensions of genrefication in the scenes in question, and closes by suggesting how a better understanding of this shift at an empirical level can inform an ongoing rethinking of the interaction between technology and aesthetics among scholars, policy makers, and musicians.

Native Classical: Musical Modernities, Indigenous Research Methodologies and a Kanienkéha (Mohawk) Concept of Non:wa (Now) - Witzleben, John Lawrence (Université du Maryland, 2014)
In this dissertation I explore how Indigenous methodologies that foreground cultural advocacy, revitalization, and education can be articulated using Indigenous language and cultural metaphor in research on North American Indian composers. Toward this end, I apply the Kanienkéha (Mohawk) concept of "non:wa" or "now" that also refers to three modes of perception–the now of the past, the present, and the future–toward understanding the intersection of innovation and tradition in classical Native music. This research joins the existing discourse that critiques binary oppositions separating Indigenous tradition (as past) and innovation (as present and future). Through interviews, fieldwork, and musical analysis, I illustrate Native values of interconnectedness, relationality, continuity, politics, and soundscapes in the processes of Native composition as well as the resultant works, I explore how these, in turn, may be understood through the application of Indigenous research techniques. In collaboration with a cohort of contemporary musicians, I look primarily at two Navajo composers–Raven Chacon and Juantio Becenti–and examine my own work as a composer, performer, and ethnomusicologist of Kanienkéha descent to explore the following questions: How can the topic of classical Native music best be served by using Indigenous methodologies in fieldwork, research, and representation and What is classical Native Music and is it different from other contemporary classical music styles? Drawing on the teachings of Indigenous dotahs (elders/teachers), the scholarship of ethnomusicologists, and examining oral and written tradition while using language and cosmology as cultural metaphors, I present a variety of possibilities for looking at Indigenous music through Indigenous eyes. Rather than offering a set of conclusions, I offer a set of tools for discussion and reflection: 1) how we might understand a definition of classical Native music; 2) how we are part